Retaining Core Staff:: The impact of human resource practices on organisational commitment - Chew, Janet; Girardi, Antonia; Entrekin, Leland (Journal of Comparative International Management)

(untitled) (Management Futures, 2005)
Abstract As organisations battle to get the most from their existing people in an environment characterised by skill shortages, the role of human resource practices in fostering employee engagement and commitment is paramount. This paper reports the findings of an Australian study, which examined the current relationship between human resource management practices and the retention of core (critical) employees working in nine organisations. This research specifically, reports on the conditional nature of the relationship between organisational and human resource practices, and commitment. The findings of the study have important implications for human resource academics and practioners.